Implementation of Punch Machines to Improve Capacity and Reduce Product Defect Rates for Soto Tiffin Handles - Putu Eka Dewi Karunia Wati; Hery Murnawan; Vava Surya Pambudi; Wandah Widyantika (International Conference of Innovation and Community Engagement, 2025)
UD. Gadjah Delta is an industry that manufactures kitchen equipment, including soto containers, with a production capacity of up to 1,400 - 1,500 pieces per day. The production process for the soto container begins with cutting the raw material, bending the left and right edges, perforating the handle ends, and finally, cutting a half-circle at the handle ends. The perforation and cutting of the handle ends are carried out using two manual machines operated by two operators. The production results from these two machines have shown a relatively high reject rate. The design of a punch machine, as developed in previous research by Wati & Hery (2023), led to a significant increase in production. Based on this research, this community service project is implementing the design by creating a punch machine that performs both perforation and cutting of the soto container handles simultaneously. The newly designed punch machine can produce more output than before, reaching 375-380 pieces per hour. Additionally, it reduces the need for operators, previously requiring two, which results in a cost saving of IDR 77.4 per piece.